Circulating biomarkers to identify cardiometabolic complications in patients with Obstructive Sleep Apnea: A systematic review. (April 2019) - Peres, Bernardo U.; Hirsch Allen, AJ; Fox, Nurit; Laher, Ismail; Hanly, Patrick; Skomro, Robert; Almeida, Fernanda; Ayas, Najib T.; ,
Summary: Untreated Obstructive sleep apnea (OSA) is associated with an increased risk of cardiometabolic diseases such as diabetes and myocardial infarction. However, it is difficult to predict which patients are at particularly high risk. This systematic review aimed to identify potentially useful circulating biomarkers that could predict cardiometabolic complications in OSA. We searched Cochrane (EBM), EMBASE, Medline, PubMed, and Web of Science databases. Search concepts included: "Obstructive Sleep Apnea", "Biomarkers" and "Risk-Stratification". Manuscripts were included if they studied adults with OSA, circulating (blood) markers, and relationships with clinical outcomes. After screening, 10 were included. Studies addressed cardiovascular disease, type 2 diabetes, end-stage renal disease and metabolic syndrome. In general, levels of inflammatory markers, adhesion molecules, and vascular proteins were associated with the presence of cardiometabolic disease in OSA patients. Although studies regarding prognostic circulating biomarkers in OSA are limited, a number of potentially promising biomarkers were identified in our review. However, more research is needed using prospective cohorts to determine which biomarkers are most robustly associated with and useful in predicting future cardiovascular and metabolic sequelae in OSA patients. Identification of such biomarkers could guide more selective and targeted therapy for OSA in an emerging era of precision-based medicine.